The construction of a swept-frequency polarimeter for observing decametric radiation from Jupiter - Baker, Dirk E. (Rhodes University, Faculty of Science, Department of Physics)
This thesis describes the design and construction of a swept-frequency polarimeter for observing Jupiter's decametric radiation in the frequency range from 15 to 45 MHz. The frequency band is tuned in two parts using two receivers for observing the left- and right-circular components of the radiation in the 15 to 26 MHz range and two receivers for observing the circular components in the 30 to 45 MHz range. The receivers are tuned electronically by means of varactor diodes and are of novel design in that they do not have any intermediate-frequency stages. The frequency band can be swept 10 times per second or 100 times per second. The antennas used for the polarimeter are helical beam antennas, two for each of the circular components in the 15 to 26 MHz range and two for the 30 to 45 MHz range. Model studies of the antennas were conducted to establish whether they have suitable characteristics for observing the polarisation of Jupiter's decametric radiation over a wide frequency range. Many spectral records of Jupiter's decametric radiation were obtained using a preliminary version of the swept-frequency receiver and a log-periodic dipole antenna. Some of the records are presented and one record which shows an interesting case of Faraday rotation is analysed.
Keywords: Polariscope; Jupiter (Planet) Radiation; Faraday effect